Seeds and the City: The Interdependence of Zoochory and Ecosystem Dynamics in Urban Environments - Gelmi-Candusso, Tiziana A.; Hämäläinen, Anni M. (Frontiers in Ecology and Evolution, 2019)
The increasing urban sprawl has contributed to the extensive fragmentation and reduction of natural habitat worldwide. Urbanization has a range of adverse effects on ecosystem functioning, including the disruption of plant dispersal processes across the landscape. Urban fragmentation can alter the distance and directionality of dispersal, leading to disrupted gene flow among populations. The dispersal processes of plants that rely on animal-mediated dispersal (zoochory) may be disproportionately affected by urbanization, as many animals avoid urban areas or restrict their movements within urban habitats. This could alter the efficiency of animal dispersal vectors and modify seed movements across urban habitats. While recent studies suggest that seed dispersal networks can be complex and dynamic even in highly managed green areas with relatively low biodiversity, zoochory in urban environments remains understudied. We synthesize the existing literature on zoochory in urban environments and place the findings in the context of ecosystem dynamics. We assess the ecological and evolutionary consequences for seed dispersal following urbanization by considering how zoochory is affected by specific features of urban environments. These include the complexity of habitats with varying continuity; high disturbance and intense management; a high proportion of alien species combined with low natural biodiversity; animal behavioral adjustments in different urban settings; and rapid evolutionary change due to urbanization. We conclude that 1) urbanization can disrupt and alter zoochory processes; and 2) successful zoochory can, in turn, alleviate or worsen the challenges to ecosystem dynamics originating from increased urbanization. The dynamic urban seed dispersal networks are emerging as useful models for the adaptability of seed dispersal communities. Their study can also shed light on eco-evolutionary processes under anthropogenic selective pressures, including species interactions. Finally, urban zoochory processes are critical to the functioning of urban ecosystems and as such, constitute an important ecosystem service with management implications. We propose directions for further research into urban zoochory processes to ensure the maintenance of ecosystem dynamics as urbanization continues.